Body mass index changes after fecal microbiota transplantation for recurrent infection - Kanika Sehgal; Parul Berry; Janice Cho; George Saffouri; Ross A. Dierkhising; Eric Battaglioli; Purna C. Kashyap; Darrell Pardi; Sahil Khanna (Therapeutic Advances in Gastroenterology)
Background: Fecal microbiota transplantation (FMT) is a successful therapy for Clostridioides difficile infection (CDI). FMT from overweight donors is speculated to influence the recipient’s body mass index (BMI) after administration for CDI. Objectives: We investigated changes in the recipient’s BMI after FMT in relation to the donor’s BMI. Design: We conducted a retrospective cohort study involving patients who underwent FMT for recurrent CDI at Mayo Clinic between 2012 and 2019. Methods: We analyzed demographic and donor data for patients undergoing FMT at Mayo Clinic (2012–2019). Recipient BMI (pre- and post-FMT) and donor BMI were extracted from medical records. Mixed-effects linear regression was used to evaluate the impact of donor BMI, donor BMI category, recipient baseline BMI, time before and after FMT, and interactions between these variables on overall BMI change and BMI change per month. Kaplan–Meier curves were used to assess BMI changes (⩾5 units) based on the last recorded post-FMT BMI. Results: We analyzed data from 401 patients with recorded BMI measurements before and after FMT. The median age of the recipients at the time of FMT was 59.1 years (interquartile range (IQR): 40.5–70.1 years), with 61.6% being female. The median BMI for recipients prior to FMT was 26.7 kg/m² (IQR: 22.7–31.6 kg/m²), while the median BMI of the donors was 24.5 kg/m 2 (IQR: 23.9–27.5 kg/m 2 ). Stool from donors with a normal BMI was used for 58.2% of recipients, while 41.8% received stool from pre-obese donors. Donor BMI data were missing for 3.2% of recipients. Donor BMI was not significantly associated with changes in recipient BMI; for each 1-unit increase in donor BMI, a 0.01-unit monthly increase was observed (95% confidence interval: −0.0003, 0.02; p  = 0.11). The log-rank test for BMI increases (⩾+5) and decreases (⩽−5) revealed no significant differences among the donor BMI groups (Chi-squared = 4.4, p  = 0.1 for increases, Chi-squared = 2, p  = 0.4 for decreases). Conclusion: The lack of impact of donor BMI on BMI changes post-FMT suggests that these changes are more dependent on the recipient’s metabolic profile. Prospective, controlled trials are required to analyze these results more comprehensively.